2020
DOI: 10.1088/1757-899x/869/6/062038
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Reasonable Degree of Specialization of Russian Companies Participating in NPP Construction Abroad

Abstract: NPP construction projects are distinguished by long construction periods (5-7 years), huge investments (up to 30 billion US dollars), and exposure to negative factors affecting the entire commissioning period and project cost. The complexity of the project management of such mega-project requires a set of special techniques and strong analytical and methodological support of decision-makers. The article discusses the practical aspects of identifying a reasonable degree of specialization of participating contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some of the works carried out by the authors of this article demonstrated the importance of the formalization of simulation and management processes for the organizational risks during the pre-investment stage of nuclear facility construction in the global market [18][19][20]. The structure of Russian sales strategies for nuclear projects in the global market [21], as well as the analysis of the project and risk management specifics for the industrial construction in foreign countries, are of key importance [22].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the works carried out by the authors of this article demonstrated the importance of the formalization of simulation and management processes for the organizational risks during the pre-investment stage of nuclear facility construction in the global market [18][19][20]. The structure of Russian sales strategies for nuclear projects in the global market [21], as well as the analysis of the project and risk management specifics for the industrial construction in foreign countries, are of key importance [22].…”
Section: Introductionmentioning
confidence: 99%
“…A significant contribution to the promotion of the Russian Federation interests in the global nuclear power plant market has made a significant devaluation of the national currency along with a scientific and technical potential of the domestic nuclear, which stimulated exports [6] and defind the high profitability of construction energy blocks NPP by Russian specialists. However, this factor is a time-limited and cannot be used in the long term.…”
Section: Introductionmentioning
confidence: 99%